Conservation and the classroom - S Lloyd (Southern African Journal of Environmental Education, 1986)
This article describes an 'environmental awareness' course presented in Kimberley by the McGregor Museum at the Teachers' Centre. Two of the successful outings which occurred as a result of this course are also described.